Dampak Kekerasan Seksual Terhadap Konstruksi Makna Pernikahan pada Perempuan Dewasa - Naila Rosdiana Zulfany; Mulya Virgonita IW; Margaretha Maria Shinta Pratiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Sexual violence against women not only impacts physical and mental health but also fundamentally alters how they understand and construct meaning around the institution of marriage. This study aims to analyze the impact of sexual violence on marriage meaning construction among adult women through a systematic literature review method. Literature search was conducted through PsycINFO, PubMed, Scopus, Web of Science, and JSTOR databases with inclusion criteria of articles published in 2010-2024, focusing on adult women survivors of sexual violence, and relevant to marriage meaning construction. Results reveal dramatic transformation in marriage meaning construction, where the concept of marriage as a